Aid for Trade: Global and Regional Perspectives - Lombaerde, Philippe (Springer, 2017)
Aid for Trade (AfT) has become a major item on the international trade and development discourse. This is to a large extent in response to concerns expressed by developing countries and economies in transition with regard to their capacities to implement trade agreements, especially WTO agreements, and undertake necessary adjustments to increase net development gains from emerging trade opportunities. In this World Report, major UN agencies active in development cooperation and longstanding providers of trade-related technical assistance and capacity building discuss ways to sustain the momentum towards the operationalization and implementation of the AfT initiative and the supportive role to be played by the UN system. This is consistent with UN's role in promoting development and helping to achieve poverty reduction, as committed in the Millennium Declaration and the 2005 World Summit Outcome. The Report should be of particular interest to government officials, officials of regional organizations, representatives of the private sector dealing with trade agreements and negotiations, civil society and academia. Supachai Panitchpakdi, Secretary-General of UNCTAD